Public Policy Evaluation of Free Health Social Security: Social Equity, Governance, and Access in Maluku Province - Fajar Pelu; Mohamad Arsad Rahawarin; Hengky Virgo Richardo Pattimukay (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study evaluates the implementation of the free public health insurance program managed by the Maluku Provincial Health Office, focusing on policy performance, social equity, governance capacity, and access for low-income and vulnerable communities in an archipelagic setting. Methodology: This study employed a descriptive qualitative approach with a public policy evaluation design. Data were collected through observation, in-depth semi-structured interviews, and document analysis. Informants were selected purposively from health officials, program administrators, and beneficiary communities. Data were analyzed through data reduction, thematic categorization, data display, conclusion drawing, and source triangulation. Main Findings: The program reduces financial barriers and improves formal access to health services for disadvantaged groups. Administrative performance is relatively effective, particularly through same-day activation and interagency verification mechanisms. However, fiscal limitations, uneven health infrastructure, data governance problems, weak information dissemination, and geographic fragmentation across islands continue to limit substantive equity. Novelty/Originality of this study: This study provides a theory-based evaluation of provincial-level health insurance implementation using William N. Dunn's policy evaluation framework. It explicitly links effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy to welfare state theory, social protection, distributive justice, decentralized governance, and spatial access in an archipelagic region.